2022
DOI: 10.1073/pnas.2103527119
|View full text |Cite
|
Sign up to set email alerts
|

The ectomycorrhizal fungus Pisolithus microcarpus encodes a microRNA involved in cross-kingdom gene silencing during symbiosis

Abstract: Small RNAs (sRNAs) are known to regulate pathogenic plant–microbe interactions. Emerging evidence from the study of these model systems suggests that microRNAs (miRNAs) can be translocated between microbes and plants to facilitate symbiosis. The roles of sRNAs in mutualistic mycorrhizal fungal interactions, however, are largely unknown. In this study, we characterized miRNAs encoded by the ectomycorrhizal fungus Pisolithus microcarpus and investigated their expression during mutualistic interaction with Eucaly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 52 publications
0
37
0
Order By: Relevance
“…Indeed, RdDM is essential in Arabidopsis to establish a beneficial relationship with the root-colonizing Trichoderma atroviride while DNA methylation and histone modifications are required for plant priming by the beneficial fungus against B. cinerea (Rebolledo-Prudencio et al ., 2021). Importantly, it was just recently shown that during the mutualistic interaction of the ectomycorrhizal fungus Pisolithus microcarpus with Eucalyptus grandis , a fungal miRNA, Pmic_miR-8, targets the host NB-ARC domain containing transcripts in a cross-kingdom RNAi manner (Wong-Bajracharya et al ., 2022). Reminiscent of this, an in silico study predicted that the beneficial arbuscular mycorrhizal fungi Rhizophagus irregularis produces sRNAs that have 237 candidate targets in the host plant Medicago truncatula , including specific mRNAs known to be modulated in roots upon AMF colonization (Silvestri et al ., 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, RdDM is essential in Arabidopsis to establish a beneficial relationship with the root-colonizing Trichoderma atroviride while DNA methylation and histone modifications are required for plant priming by the beneficial fungus against B. cinerea (Rebolledo-Prudencio et al ., 2021). Importantly, it was just recently shown that during the mutualistic interaction of the ectomycorrhizal fungus Pisolithus microcarpus with Eucalyptus grandis , a fungal miRNA, Pmic_miR-8, targets the host NB-ARC domain containing transcripts in a cross-kingdom RNAi manner (Wong-Bajracharya et al ., 2022). Reminiscent of this, an in silico study predicted that the beneficial arbuscular mycorrhizal fungi Rhizophagus irregularis produces sRNAs that have 237 candidate targets in the host plant Medicago truncatula , including specific mRNAs known to be modulated in roots upon AMF colonization (Silvestri et al ., 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the miRNA, Pmic_miR-8, was found to be transported from a fungal symbiont, Pisolithus microcarpus , to the roots of its symbiotic host, Eucalyptus grandis ( Wong-Bajracharya et al., 2022 ). Pmic_miR-8 may inhibit the host transcripts encoding an NB-ARC domain-containing disease resistance protein, to stabilize the symbiotic interaction ( Wong-Bajracharya et al., 2022 ).…”
Section: Future Perspectivesmentioning
confidence: 99%
“…A special case of inter-organismal communication is the exchange of information between organisms of different taxa. Examples of this phenomenon in the area of plant-microbe interactions comprise mutually advantageous symbioses and diseases caused by pathogenic fungi (1, 2). Gene regulation by non-coding small RNAs (sRNAs) can play an important role in the context of such plant-microbe encounters (1).…”
Section: Introductionmentioning
confidence: 99%